PROVISION OF REMOTE BANKING SERVICES IN UZBEKISTAN ANALYSIS OF ITS PRACTICE - Zokir Mamadiyarov (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This article analyzes the emergence of remote banking services in Uzbekistan, the current situation, the development trends in the banking sector. The results of this study include the study of the current state of remote banking services, the formation of conclusions from the results and the development of scientific proposals